Viscoelastic behavior of olive oil-in-water emulsion stabilized by sucrose fatty acid esters - Tan, H.W.; Misran, M.; Khoo, S.K. (2011)
The rheological behavior of the olive oil-in-water emulsions has been studied by varying the oil to water ratio as well as the surfactant concentration. The viscoelastic property of the olive oil emulsions was investigated with a cone-and-plate system, using a Bohlin C-VOR Rheometer. The obtained results indicated that the emulsions with greater oil and surfactant concentrations are highly packed systems with greater interdroplet interactions as well as higher critical strain. The viscoelastic property of the emulsions can be enhanced by increasing the oil concentration. The elastic modulus of the emulsions was always predominant over the viscous modulus, thereby emphasizing the elastic character of the above mentioned emulsions. The emulsion with a higher oil composition shows greater elasticity, which implies a strong dynamic rigidity of the emulsions. A high oil composition also enhanced the structural integrity as well as the interdroplet interactions of the emulsion.